2003
DOI: 10.1023/b:boli.0000009921.42503.c2
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal screening for cystic fibrosis: France rises to the challenge

Abstract: This paper describes the adjustments to the French neonatal screening programme required by the introduction of systematic screening for cystic fibrosis (CF), taking into account both the legal and statutory framework and the lessons of a pilot study carried out 10 years ago. The French association for the screening and prevention of infant handicaps (AFDPHE) has been mandated by its regulatory agencies to organize screening for CF in France (metropolitan and overseas territories). During the year 2001, expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 11 publications
0
15
0
2
Order By: Relevance
“…Finally, mass newborn screening using DNA analysis is problematic in countries where informed consent is requested. 6 We have previously shown that the concentration of pancreatitis-associated protein (PAP), a stress protein synthesized by the diseased pancreas, is elevated in the blood of newborns with CF. 7 But PAP elevation is not strictly specific to CF, and CF screening with PAP would have had performance similar to that of IRT alone.…”
mentioning
confidence: 99%
“…Finally, mass newborn screening using DNA analysis is problematic in countries where informed consent is requested. 6 We have previously shown that the concentration of pancreatitis-associated protein (PAP), a stress protein synthesized by the diseased pancreas, is elevated in the blood of newborns with CF. 7 But PAP elevation is not strictly specific to CF, and CF screening with PAP would have had performance similar to that of IRT alone.…”
mentioning
confidence: 99%
“…Esta melhora, no entanto, não depende apenas do laboratório, onde são realizados os exames, e/ou do ambulatório, onde são acompanhados os pacientes afetados, mas de todo um conjunto de pessoas e instituições, que engloba desde os responsáveis pela criança (mãe e/ou pai), hospital ou maternidade onde nasceu a criança, postos responsáveis pela coleta adequada das amostras e seu envio de maneira ágil, Secretarias de Saúde dos municípios (realização de campanhas de esclarecimento quanto à importância do teste) até o Serviço de Referência de Triagem Neonatal. Semelhante ao já instituído na França 33 , a adoção do 3 o dia de vida do recém-nascido como sendo o "Dia da Triagem Neonatal", associada à divulgação abrangente, poderiam representar uma estratégia para ampliar a atenção neste programa de fundamental importância para a Saúde Pública. Com isto será possível ampliar a cobertura e encurtar o tempo para o início do tratamento nas crianças afetadas, proporcionando, assim, melhores perspectivas para os afetados.…”
Section: Discussionunclassified
“…In some countries, the inclusion of DNA-based testing techniques in the CF screening algorithm required procedures to be brought into line with laws on bioethics, initially established to protect individual rights to privacy (Farriaux et al 2003). One of the main consequence is the need to obtain a written consent to perform the test, with a risk that the parents refuse the test!…”
Section: Ethical Considerationsmentioning
confidence: 99%